1997
DOI: 10.1002/(sici)1098-2280(1997)30:4<363::aid-em1>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mitomycin C-induced micronuclei in lymphocytes from malnourished infected children

Abstract: The purpose of this study was to determine if peripheral blood lymphocytes from malnourished children with gastrointestinal or respiratory bacterial infection show increased frequencies of Mitomycin C (MMC)‐induced micronuclei as compared to well‐nourished, infected children. The results indicate that cells from malnourished, infected children had greater chromosome damage. This may indicate that such children would be more susceptible to environmental damage and malignant transformation. Micronucleus frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
0
8
1
3
Order By: Relevance
“…It has been suggested that cells of malnourished children are more susceptible to environmental damage [Ortiz et al, 1997]. Although statistical analysis carried out in this study does not support an overall greater susceptibility in malnourished lymphocytes to DNA damage induced by peroxide, clearly these children showed the highest proportion of highly damaged cells after H 2 O 2 treatment (Fig.…”
contrasting
confidence: 52%
See 1 more Smart Citation
“…It has been suggested that cells of malnourished children are more susceptible to environmental damage [Ortiz et al, 1997]. Although statistical analysis carried out in this study does not support an overall greater susceptibility in malnourished lymphocytes to DNA damage induced by peroxide, clearly these children showed the highest proportion of highly damaged cells after H 2 O 2 treatment (Fig.…”
contrasting
confidence: 52%
“…Sister-chromatid exchange analyses (SCE) have provided controversial data: whereas Mutchinick et al [1979] found that SCE frequencies were similar in well-nourished and malnourished children, Murthy and Rahiman [1983] and Ortiz et al [1994] observed significantly higher SCE frequencies in children with malnutrition. The basal frequency of micronuclei was greater in PCM children than in well-nourished controls, and lymphocytes of malnourished children showed greater susceptibility to mitomycin C-induced damage [Ortiz et al, 1997]. Furthermore, increased DNA damage in malnutrition has been detected by the single-cell gel electrophoresis technique (SCGE or comet assay), although the damage was also associated with the presence of infection and drug treatments [Betancourt et al, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…Los ensayos cometa y de MN han sido de gran utilidad y han aportado valiosa información para el entendimiento de los efectos de la DN. Se ha observado que la DN causa daño al ADN, mismo que puede estar asociado con la presencia de infecciones y tratamientos farmacológicos a los que se someten los niños que presentan DN (Betancourt et al, 1995;Ortiz et al, 1997).…”
Section: Estudios Citogenéticos Y Desnutriciónunclassified
“…Two week-old UN and WN male Han-Wistar rats were treated daily with 0, 20, or 40 mg/kg ENU for 3 consecutive days. Blood was collected from the tail vein one day before ENU treatment (Day-1) and after ENU administration on Days 7,14,21,28,35,42,49,56 and 63. Pig-a MFs were measured in RETs and RBCs as the RET CD59− and RBC CD59− frequencies.…”
Section: Perspectivasmentioning
confidence: 99%
See 1 more Smart Citation